A Concise Synthesis of (±)-Methoxyfumimycin Ethyl Ester. (June 2014) - Zhou, Zhiwang; Hu, Yu; Wang, Bin; He, Xiaoru; Ren, Gang; Feng, Lihua
The protecting-group-free synthesis of (±)-methoxyfumimycin ethyl ester, a potential bacterial peptide deformylase (PDF) inhibitor, is reported. The synthetic approach features a tandem Friedel–Crafts alkylation/lactonisation access as a key reaction to generate α, α-disubstituted amino acid unit.